Research and development of intelligent bypass ring net cage and collaborative control technology of multi-source power supply system in flooded environment - Zhanhua Huang; Liang He (Energy Informatics)
Abstract With the acceleration of urbanization, urban waterlogging has become increasingly serious, posing new difficulties to the stability and safety of the power system. Given this, a new type of waterproof circular net cage is designed to ensure power supply and maintain voltage stability by switching to a bypass during floods. The improved non-dominated sorting genetic algorithm optimizes multi-source power supply systems. This results in the provision of innovative solutions for power systems and multi-source power supply collaborative control in flooded environments. Simulation experiments have demonstrated that, under conditions of mild flooding, the voltage of the ring net cage remained at approximately 400 V. In the case of severe flooding, the voltage of the ring net cage was switched to the bypass backup circuit and the voltage was maintained at around 220 V. The current changed with the load. The minimum comprehensive operating cost of the multi-source power supply system optimized based on the improved non-dominated sorting genetic algorithm was 1,453 yuan. Optimization strategies could reduce the unbalanced power of the system and increase the utilization rate of renewable energy to over 90%. The intelligent bypass net cage design has new features of automatic switching of bypass and maintaining voltage stability during floods. Combining an improved non-dominated sorting genetic algorithm for optimizing multi-source power supply systems can significantly reduce operating costs and greatly improve the utilization of renewable energy. The study provides an innovative solution for power systems in flood environments and theoretical support for multi-source power supply collaborative control technology.